2021
DOI: 10.1016/j.conbuildmat.2021.123573
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the hydration of reactive MgO cement blends incorporating different magnesium carbonates

Abstract: h i g h l i g h t sMg(OH) 2 surface-layers limit the further hydration of reactive MgO cement (RMC). Use of magnesium acetate (MA), hydromagnesite (H) and magnesite (M) improved RMC hydration. MA and M enhanced the morphology of hydration products. Simultaneous use of MA and M improved the compressive strength by 240%. Low-crystallinity Mg(OH) 2 with a bird nest-like structure was observed in RMC-H samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…69 Alternatively, the CO 2 capture within hydrated reactive MgO cements results on the precipitation of hydrated Mg carbonates (mainly nesquehonite, and hydromagnesite), which have the binding properties necessary to develop a dense microstructure network with the strength required in cementitious materials. 152 As a matter of fact, the strength development of the reactive MgO cements based cements has been demonstrated to be higher than the ordinary Portland cement (OPC) counterparts with similar composition. 153 The carbonation of MgO is usually associated with conditions of high pressures and temperatures, but the process conditions can be tuned according to the morphological properties of the MgO precursors.…”
Section: Applications Of Mg Carbonates In Construction Materialsmentioning
confidence: 99%
“…69 Alternatively, the CO 2 capture within hydrated reactive MgO cements results on the precipitation of hydrated Mg carbonates (mainly nesquehonite, and hydromagnesite), which have the binding properties necessary to develop a dense microstructure network with the strength required in cementitious materials. 152 As a matter of fact, the strength development of the reactive MgO cements based cements has been demonstrated to be higher than the ordinary Portland cement (OPC) counterparts with similar composition. 153 The carbonation of MgO is usually associated with conditions of high pressures and temperatures, but the process conditions can be tuned according to the morphological properties of the MgO precursors.…”
Section: Applications Of Mg Carbonates In Construction Materialsmentioning
confidence: 99%
“…Furthermore, the high amounts of unreacted MgO and Mg(OH)2 could cause concerns about volume stability in the long-term as these phases could hydrate and carbonate at later ages, potentially causing excessive expansion. While previous studies reported that the low-crystallinity Mg(OH)2 froming in RMC-H samples could be prone to carbonation [44], the extent of this under a CO2 intensive environment has not been investigated. As these disadvantages could inhibit the application of RMC in the construction industry, it is critical to identify solutions for improving the utility and hence the carbonation potential of RMC, which will enable higher degrees of CO2 sequestration and lower carbon footprints.…”
Section: Introductionmentioning
confidence: 97%
“…When scaled up, this route will present a promising route for the production of M from magnesium silicate minerals, which will reduce CO2 emissions associated with cement production. Furthermore, the simultaneous use of magnesium acetate and M was reported to improve the compressive strength of RMC samples by 240% [44]. While these advantages make M an attractive material to be used in RMC formulations, its influence on the carbonation mechanisms, and associated performance and microstructural development has not been studied until now.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have proven the superior influence of FA and MEA on performance despite a lack of clarity on the related hydration mechanism. Meanwhile, prior studies are based on the curing at 20 °C, which is inconsistent with the high-temperature environment inside dam concrete (Dung and Unluer, 2021;Cao and Al-Tabbaa, 2022).…”
Section: Introductionmentioning
confidence: 99%